COVID-19 AND THE MANAGEMENT OF THE ECONOMY OF ODISHA - Das, Sanjukta; Banoo, Saida (International Journal of Research -GRANTHAALAYAH, 2020)
Occurrence of COVID-19 pandemic and the policy measures taken from time to time to contain its spread have brought a huge loss to the economy. In this paper an attempt is made to analyse these by taking the case of Odisha which is one of the States in India that have taken proactive role in managing the COVID-19 related disaster. It discusses the Government policy of lock down in the country and Odisha. This is followed by an analysis of the effect of Lock down on the economy and livelihood. Then it tries to suggest some steps for managing the economy in this situation. Here it mainly emphasizes the local economy model for sustainable management of the economy.